A prerrogativa do inusitado: o estatuto da ação em Bergson - Galvão, Jadir Mauro (2011)
When getting deeper in the general thought of the meaning of Time, Bergson not only finds out a particular way in which our Intelligence functions but also discovers that this functioning interferes heavily in our view of the world, both our actions and our daily decisions. It happens as a narrowing of our range of vision which imposes a limit to our actions, as well as to our expectations. We depict the world in our conscience, but only that specific part which is coherent to our concepts, and also only what we can translate through language. From that on, our actions will be always based on the same concepts already solidified in the past, and will always be described by language. This will only bring us repetitions. Choosing Intuition as the way to keep contact with reality, Bergson searches for removing the obstacles which Intelligence has introduced only for the sake of calculations, measurements and predictions, which have become a filter to reality. When we remove the symbolic intervention, we will have a more complete view of the world that surrounds us, and also a truly open field for our actions. If, for Bergson, the concept of Duration is a more trustworthy way to translate reality than the concept of Time, it is not less true for him that the past consubstantiates the present in an inseparable interpenetration which turns into a unique and singular present. Also, more than just another distinct element in the conceptual web, the future is not there to be revealed, but to be started, to be created, filled with something unexpected, not only as some clay modeled by our past experiences, but as a blank screen ready to receive creative strokes by us, the artists